PENINGKATAN KINERJA UMKM MELALUI INOVASI HIJAU, PEMASARAN DIGITAL, DAN KEBIJAKAN PEMERINTAH DI KABUPATEN SUMBAWA - Wahyu Haryadi; Ismawati; Nurdin Natan; Kamaruddin (Berajah Journal, 2026)
The purpose of this study is to test and analyze the influence of green innovation, digital marketing, and government policies on improving the performance of micro, small, and medium enterprises (MSMEs) in Sumbawa Regency. This type of research is associative with a quantitative approach. The data collection technique was through questionnaires using a purposive sampling method. This study involved 100 MSME owners/managers. The results of the study indicate that partially and simultaneously there is a positive and significant influence of green innovation, digital marketing, government policies and improving MSME performance. Based on the results of the determination coefficient test, an R Square value of 0.401 was obtained, which means that the variables of green innovation, digital marketing, and government policies are able to explain variations in MSME performance by 40.1%, while the remaining 59.9% is explained by other factors outside the research model.